Status of Some Minerals in Patients with Polycythemia using Colorimetric Method - Abbas, Ahsan K.; Al-Sayab, Mohammed S.; Majeed, Mayssa J. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Polycythemia (or polycythaemia or erythrocytosis) is a condition in which there is a net increase in the total number of blood cells, primarily red blood cells, in the body. The overproduction of red blood cells may be due to a primary process in the bone marrow (a so-called myeloproliferative syndrome), or it may be a reaction to chronically low oxygen levels or, rarely, a malignancy. Minerals are the building blocks of our bodies. They are required for body structure, fluid balance, protein structures and to produce hormones. They are the key for the health of every body system and function. They act as co-factors, catalysts or inhibitors of all enzymes in the body . Patients and Methods: Blood Calcium, iron & Magnesium concentrations was determined by using colorimetric method, while Potassium, Copper& Zinc concentration was determined by using flam atomic absorption spectrometry method. Results: Obtained results showed that the level of Potassium, Calcium and zinc in polycythemic subjects were significantly higher than that of healthy subjects (p<0.05), while serum iron, Copper in polycythemic subjects were significantly lower than that of healthy subjects. Magnesium level shows no significant difference between two studied groups. Conclusion: Recent research indicates that minerals may play a significant role against a variety of degenerative diseases and processes.